2000
DOI: 10.1016/s0925-2312(00)00286-1
|View full text |Cite
|
Sign up to set email alerts
|

Blind source separation of multichannel neuromagnetic responses

Abstract: Magnetoencephalography (MEG) is a functional brain imaging technique with millisecond temporal resolution and millimeter spatial sensitivity. The high temporal resolution of MEG compared to fMRI and PET (milliseconds vs. seconds and tens of seconds) makes it ideal for measuring the precise time of neuronal responses, thereby o!ering a powerful tool for studying temporal dynamics. We applied blind-source separation (BSS) to continuous 122-channel human magnetoencephalographic data from two subjects and "ve task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…As shown in Figures 2 and 3, by applying SOBI to MEG data we achieved excellent separation of noise (Tang et al, 2000a), resulting in signal-to-noise improvement sufficient to perform single trial onset detection (Tang et al, 2000b), and we showed that neuronal components can be separated from each other and localized in a robust (across modalities, tasks, and subject) fashion . These results are surveyed by .…”
Section: Separationsupporting
confidence: 59%
“…As shown in Figures 2 and 3, by applying SOBI to MEG data we achieved excellent separation of noise (Tang et al, 2000a), resulting in signal-to-noise improvement sufficient to perform single trial onset detection (Tang et al, 2000b), and we showed that neuronal components can be separated from each other and localized in a robust (across modalities, tasks, and subject) fashion . These results are surveyed by .…”
Section: Separationsupporting
confidence: 59%
“…BSS of MEG data segregates noise from signal [Sander et al, 2002;Tang et al, 2000a;Vigário et al, 2000], raising the SNR sufficiently to allow single-trial analysis [Tang et al, 2000b]. Although the sensor attenuation vectors of BSS-separated components can be localized well to equivalent current dipoles [Tang et al, 2002;Vigário et al, 2000], the recovered field maps can be quite noisy.…”
Section: Localization On Real Meg Signals and Comparison With Commercmentioning
confidence: 99%
“…One such technique that we have used is blind source separation (BSS). BSS has been shown to segregate neuronal from nonneuronal signals, and neuronal signals from each other, in both EEG [Jung et al, 2000a, b;Makeig et al, 1997Makeig et al, , 1999 and MEG [Cao et al, 2000;Tang et al, 2000aTang et al, ,b, 2002Tang and Pearlmutter, 2003;Vigário et al, 1998Vigário et al, , 1999Vigário et al, , 2000Wü bbeler et al, 2000;Ziehe et al, 2000]. For these reasons, despite its limitations, it seems feasible to use the localizer proposed above as a stage in a practical robust real-time MEG processing pipeline.…”
Section: Figure 12mentioning
confidence: 99%
“…Superconducting QUantum Interference Device (SQUID) sensors used in the latter technology are susceptible to magnetic coupling due to geometry and must be shielded carefully against magnetic noise. Deconvolution techniques are used to separate different noise sources and ameliorate the effect of electrical and magnetic coupling in these devices [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%